Imagining religious toleration : a literary history of an idea, 1600-1830 - Conway, Alison; Alvarez, David, 1966- (University of Toronto Press, 2019)
"Current debates regarding religious tolerations have come to a standstill. In investigating the eighteenth-century novel, Alison Conway, David Alvarez, and their contributors shed light on what literature can say about toleration, and how it can produce and manage feelings of tolerance and intolerance. Largely reserved for intellectual historians and political philosophers, discussions of religious toleration are relatively limited, with very few literary scholars exploring the subject. Beginning with an overview of the historical debates surrounding the terms "toleration" and "tolerance," this book moves on to discuss the specific contribution that literature and literary modes have made to cultural history, studying the literary techniques philosophers, theologians, and political theorists used to frame the questions central to the idea and practice of religious toleration. By tracing the rhetoric employed by a wide range of authors, this book reveals the tropes and figures we associate with literary texts, delving into such topics as conversion as an instrument of power in Shakespeare's The Merchant of Venice and the relationship between religious toleration and the rise of Enlightenment satire."--